PENDOKUMENTASIAN TARI PABBITTE PASSAPU KAJANG KABUPATEN BULUKUMBA (Sebagai Upaya Pelestarian Tari Tradisional) - Rahma M; Asia Ramli; Muh. Kurniawan (Universitas Negeri Makassar, 2022)
This study aims to document dance as a form of preservation of traditional dance with a theoretical approach. Dance documentation includes data collection carried out directly in Tanatoa Village by meeting the original actors, then conducting interviews and demonstrations and recording dances, then processing data by recording in the form of writing. dance moves in detail, descriptions of the moves accompanied by photos and floor patterns, as well as dissemination by documenting the results of this research in the form of reports and conducting scientific publications at national seminars, in the form of proceedings and journals and publishing on social media YouTube so that it can be easily accessed by students and the general public and included in the library, both regional and faculty libraries, so that students and the general public can easily obtain data related to the Pabitte Passapu Dance, which consists of 12 varieties, namely i, Akkokoroa, Angngibeng, Appakeha, Appalotteng, Sekko Taji, Paganti, A, pabitte, Tannang ulumanu, A,laga, Angngera Seha' complete with photos and floor patterns.Keyword: Dance documentation, Pabitte Passapu danceThis study aims to document dance as a form of preservation of traditional dance with a theoretical approach. Dance documentation includes data collection carried out directly in Tanatoa Village by meeting the original actors, then conducting interviews and demonstrations and recording dances, then processing data by recording in the form of writing. dance moves in detail, descriptions of the moves accompanied by photos and floor patterns, as well as dissemination by documenting the results of this research in the form of reports and conducting scientific publications at national seminars, in the form of proceedings and journals and publishing on social media YouTube so that it can be easily accessed by students and the general public and included in the library, both regional and faculty libraries, so that students and the general public can easily obtain data related to the Pabitte Passapu Dance, which consists of 12 varieties, namely i, Akkokoroa, Angngibeng, Appakeha, Appalotteng, Sekko Taji, Paganti, A, pabitte, Tannang ulumanu, A,laga, Angngera Seha' complete with photos and floor patterns.Keyword: Dance documentation, Pabitte Passapu dance